EFEKTIFITAS PEMBERIAN JUS MENTIMUN DAN REBUSAN SELEDRI TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PANGKALAN KASAI - Wiji, Rizki Natia; Yumita, Suliya; Yuningsih, Silvia Anita (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Pre elderly who had hypertension for 3 days in the working area Puskesmas Pangkalan Kasai.by giving cucumber juice has final blood pressure after it ranges in 120/84 - 120/78 from the initial inspection 150/100 mmHg and the adminidtration of celery stew has a final blood pressure range 120/80 -130/80 mmHg from the initial examination above 140/90 mmHg This study aims to determine the effectiveness of giving cucumber juice and celery stew to decrease blood pressure in hypertensive patients in the working area Puskesmas Pangkalan Kasai. The design in this study was Quasi eksperimen with design One Group pretest and posttest. This research was conducted at Puskesmas Pangkalan Kasai with 30 respondents. The sampling method used is total sampling. The measuring instrument used is the observation sheet. The analysis used is univariate and bivariate by testing paired sample t test. The result of research indicate that giving cucumber juice and celery stew influences the decrease of blood pressure of hypertension patients. The highest percentage of decrease is on celery stew group (100%). There is a differences in blood pressure pretest and posttest of cucumber and celery groups with p value < 0,05 that is as much 0,00There is a giving effect cucumber juice and celery stew the decrease of blood pressure of hypertension patients..